Hospitalitas Pendidikan Kristiani dalam Masyarakat Majemuk - Serva Tuju; Harls Evan R. Siahaan; Melkius Ayok; Fereddy Siagian; Donna Sampaleng (Sekolah Tinggi Teologi Berita Hidup, 2021)
The diversity of human identities in the context of pluralism is essential. However, differences are often seen as something